2016
DOI: 10.1186/s13613-016-0146-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of PCT in septic emergency patients

Abstract: BackgroundAn accurate assessment of septic patients at risk for poor clinical outcomes is challenging for clinicians in the emergency department (ED).Objectives We aimed to evaluate the prognostic value of procalcitonin (PCT) in septic patients in the ED for predicting death.ResultsIn a retrospective study, 188 septic patients (median age 63 [IQR 51–80]) of two French university hospitals were included. Patients who deceased within 30 days (20 %, n = 37) presented higher PCT value at admission (median 34.0 µg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 24 publications
1
20
0
2
Order By: Relevance
“…In patients with stopping advice, this occurred only in 42.3% (11/26). These results are in line with previous studies which showed that high PCT levels are associated with an unfavourable outcome [ 27 , 28 ]. Furthermore, a not adequately declining PCT is an independent predictor of mortality in septic patients [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…In patients with stopping advice, this occurred only in 42.3% (11/26). These results are in line with previous studies which showed that high PCT levels are associated with an unfavourable outcome [ 27 , 28 ]. Furthermore, a not adequately declining PCT is an independent predictor of mortality in septic patients [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Peschanski et al . found that PCT levels at admission were moderately accurate in identifying the outcome in septic patients, with 51% sensitivity and an AUC of 0.6737. Additionally, a recent meta-analysis showed that the commonly used cut-off for PCT of 0.5 ng/mL only had a sensitivity of 44% to identify patients with pneumonia who have a high risk of death38.…”
Section: Discussionmentioning
confidence: 99%
“…The studies included in this review were published from 2009 to 2019, with most of the studies being published after 2014 (90%). The following 10 studies were included in the review: Nargis et al [14], Mustafić et al [15], Cui et al [16], Lipińska-Gediga et al [17], Shokouhi et al [18], Ryoo et al [19], Peschanski et al [20], Demirdal et al [21], Tsangaris et al [22], and Yu et al [23]. Among the 10 studies, six were conducted in Asia [16,18,20,21,23] and four were conducted in Europe [15,17,20,22].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%